Analisis Akad Salam (PSAK Syariah 103) Pada Transaksi Jual Beli Online - Chandra Kurniawan; Hasbullah Eka Saputra; Yulia Dwi Safitri; Ersi sisdianto (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
From an Islamic perspective, the number of online transactions that fall under the heading of fiqh muamalah niaga or buying and selling is rapidly increasing. Islam has laws that apply to both buyers and sellers in buying and selling transactions. The purpose of this study is to examine the basic elements and requirements for implementing a greeting contract in online buying and selling transactions that comply with the Statement of Islamic Financial Accounting Standards PSAK Syariah 103. The research was conducted using qualitative methods and case study methods were conducted in the Online Store. The informants of this research are traders and consumers. The results showed that sellers generally know the pillars and conditions of buying and selling online in an Islamic perspective. Akad Salam has been carried out by business people with the term pre-order, business people do not know and apply PSAK Syariah 103. Research results can be useful for entrepreneurs, academics as well as government agencies and the community.